CHINA AND THE LONG CYCLE THEORY: Correction of Modelski’s Long Cycle Theory Through the Experience of China's Rise - Sugiarto Pramono; Liu Changming (Universitas Wahid Hasyim Semarang, 2022)
Modelski's Long Cycle Theory influences the way scholars understand the process of world political history, including the continuation of the dynamics of world politics in the future. Modelski and his scholars suggest that the facts of the 500-year history of global politics reflect the Long Cycle pattern in which a new great power emerges every 100 years after a global war. This theory is corrected by the historical facts of China's rise in the last 40 years which proves the truth of the Long Cycle Theory on the one hand but at the same time also corrects the theory. New facts tell us that the rise of China as a new great power was not accompanied by a global war as Modelski and his supporting scholars explain. The results of this study tell us that the Long Cycle of global politics needs to be corrected.Keywords: Rise of China, great power, global war, long cycle theory.AbstrakTeori Siklus Panjang Modelski berpengaruh pada cara para sarjana memahami proses sejarah politik dunia, termasuk keberlangsungan dinamika politik dunia selanjutnya. Modelski dan para cendekiawan pendukungnya menginduksikan bahwa fakta sejarah 500 tahun politik global mencerminkan pola Siklus Panjang di mana sebuah kekuatan besar baru muncul setiap 100 tahun setelah sebuah perang global. Teori ini dikoreksi oleh fakta sejarah kebangkitan China dalam 40 tahun terakhir yang membuktikan kebenaran Teori Siklus Panjang di satu sisi tetapi pada saat yang sama juga mengoreksi teori tersebut. Fakta baru memberitahu kita bahwa kebangkitan Cina sebagai kekuatan besar baru tidak disertai dengan perang global sebagaimana penjelasan Modelski dan para sarjaba pendukungnya. Hasil penelitian ini memberi tahu kita bahwa Siklus Panjang politik global perlu dikoreksi.Kata kunci: Kebangkitan Tiongkok, kekuatan besar, perang global, teori siklus panjang.